Dual mTORC1/mTORC2 blocker as a possible therapy for tauopathy in cellular model - Salama, Mohamed; Elhussiny, Mahmoud; Magdy, Alshimaa; Omran, Ahmed G.; Alsayed, Aziza; Ashry, Ramy; Mohamed, Wael Mohamed Yousef (Springer Nature, 2018)
Tauopathy comprises a group of disorders caused by abnormal aggregates of tau protein. In these disorders phosphorylated tau protein tends to accumulate inside neuronal cells (soma) instead of the normal axonal distribution of tau. A suggested therapeutic strategy for tauopathy is to induce autophagy to increase the ability to get rid of the unwanted tau aggregates. One of the key controllers of autophagy is mTOR. Blocking mTOR leads to stimulation of autophagy. Recently, unravelling molecular structure of mTOR showed that it is formed of two subunits: mTORC1/C2. So, blocking both subunits of mTOR seems more attractive as it will explore all abilities of mTOR molecule. In the present study, we report using pp242 which is a dual mTORC1/C2 blocker in cellular model of tauopathy using LUHMES cell line. Adding fenazaquin to LUHMES cells induced tauopathy in the form of increased phospho tau aggregates. Moreover, fenazaquin treated cells showed the characteristic somatic redistribution of tau. PP242 use in the present tauopathy model reversed the pathology significantly without observable cellular toxicity for the used dosage of 1000 nM. The present study suggests the possible use of pp242 as a dual mTOR blocker to treat tauopathy.